The Influence of Social Media Marketing on Purchase Intention of Compass Shoes Products through Shopee in Bandung - Sonny Dowansiba; Arie Hendra Saputro (CAKRAWALA : Management Science Journal, 2025)
This study investigates the impact of social media marketing on consumer purchase intention for Compass, a leading local shoe brand, through the Shopee e-commerce platform in Bandung. Using a quantitative, descriptive, and associative approach, data were collected via an online questionnaire from 99 purposively selected respondents and analyzed with simple linear regression in SPSS. Results reveal that social media marketing significantly influences purchase intention (β = 0.376, p = 0.003), although it accounts for only 8.6% of the variance (R² = 0.086). Despite Compass’ growing popularity on Instagram—with over 1.2 million followers—the brand experiences declining engagement rates, highlighting a gap between social media visibility and actual e-commerce conversions. This finding underscores the importance of integrating engaging digital content with practical e-commerce strategies such as product availability, logistics, and customer service. For Compass and similar local brands, effective use of social media marketing should be complemented with analytics-driven personalization and seamless customer experience to convert online hype into sustainable sales.